2013
DOI: 10.1159/000350161
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Th17/IL-17 in the Pathogenesis of Primary Nephrotic Syndrome in Children

Abstract: Background: This work aims to explore the role of Th17 and IL-17 signaling in the pathogenesis of primary nephrotic syndrome (PNS) in children and podocyte injury, children with PNS were divided into minimal change nephrotic syndrome (MCNS) and non-minimal change nephrotic syndrome [NMCNS, including mesangial proliferative glomerulonephritis (MsPGN) and focal segmental glomerulosclerosis (FSGS)]. Methods: Flow cytometry (FCM) was used to observe the circulating frequency of Th17 cells and the apoptosis of podo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 25 publications
2
69
1
4
Order By: Relevance
“…6B, C). Similarly, it was reported that rIL-17 also promoted podocyte apoptosis, and increased caspase 3 in cultured podocytes [25]. Here, phalloidin staining displayed that rIL-17 also caused disorganization of actin cytoskeleton in cultured podocytes, evidenced by the disappearance of actin filamentous and the induction of actin nucleation (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…6B, C). Similarly, it was reported that rIL-17 also promoted podocyte apoptosis, and increased caspase 3 in cultured podocytes [25]. Here, phalloidin staining displayed that rIL-17 also caused disorganization of actin cytoskeleton in cultured podocytes, evidenced by the disappearance of actin filamentous and the induction of actin nucleation (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Immunoblotting assay showed that rIL-17 led to a slight reduction of total nephrin. Nevertheless, it was reported that the same dose of rIL-17 had no effect on the expression of nephrin, but resulted in a decreased expression of another podocyte protein podocalyxin in cultured podocytes [25]. Importantly, phosphor-nephrin level was measured here by quantitative immunoblotting assay, and our data show a dramatic reduction of phosphor-nephrin by rIL-17 (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Pathogenesis of nephrotic syndrome is based on the immunological aberration, characterized by abundant circulating factor [4] and immuno-regulatory imbalance [5]. Conversely, regulatory T-cells (T Reg ) is an important tolerogenic T-cell possessing protective effect on podocyte destruction [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This disease can frequently recur in patients once it progresses to later stages, which can in severe cases lead to chronic glomerular sclerosis (Paul et al, 2014; Working Group for National Survey on Status of Diagnosis and Treatment of Childhood Renal Diseases, 2014; Ezaki et al, 2015;Geng et al, 2015;Chen and Xia, 2015;Yang and Zhang, 2015). CD4+ cells can be classified into T helper cell 1 (Th1), Th2, Th17, and CD4+CD25+ regulatory cells (Treg) in vitro (Wang et al, 2010(Wang et al, , 2013. Physiologically, there is a relatively stable dynamic equilibrium between Th17 and Treg cells, which is an antagonistic relationship.…”
Section: Introductionmentioning
confidence: 99%